2015
DOI: 10.1016/j.addbeh.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations between components of anxiety sensitivity and smoking-related characteristics

Abstract: Anxiety sensitivity (AS)—the tendency to fear anxiety-related experiences—is a risk factor for anxiety disorders and may contribute to smoking motivation and maintenance. Few studies have examined relations between conceptually distinct components of AS and smoking behavior. The purpose of the current study was to examine associations between AS components—Physical Concerns, Mental Concerns, and Social Concerns—and an array of smoking-related characteristics. In a cross-sectional design, we administered the An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
1
30
0
2
Order By: Relevance
“…[24,25] High-AS smokers report experiencing more severe withdrawal symptoms [2628] and stronger motives and expectations in regard to reducing NA by smoking, [1720] and AS associations with smoking-related variables have persisted when controlling for anxiety, depression, NA, daily cigarette use, and tobacco dependence severity. [2931] Additionally, two experimental studies have shown that high-AS individuals report greater NA reduction from smoking subsequent to laboratory-induced social stress. [32,33] Thus, it appears that AS is a risk factor for smoking largely due to its ability to heighten NA in response to stressors (e.g., tobacco withdrawal), which in turn increases negative reinforcement smoking motivation.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[24,25] High-AS smokers report experiencing more severe withdrawal symptoms [2628] and stronger motives and expectations in regard to reducing NA by smoking, [1720] and AS associations with smoking-related variables have persisted when controlling for anxiety, depression, NA, daily cigarette use, and tobacco dependence severity. [2931] Additionally, two experimental studies have shown that high-AS individuals report greater NA reduction from smoking subsequent to laboratory-induced social stress. [32,33] Thus, it appears that AS is a risk factor for smoking largely due to its ability to heighten NA in response to stressors (e.g., tobacco withdrawal), which in turn increases negative reinforcement smoking motivation.…”
Section: Introductionmentioning
confidence: 99%
“…[6,35,36] Yet, relatively few studies have examined smoking variables in relation to the three AS facets, and extant work shows that different facets of AS have different smoking-related correlates. AS physical and cognitive concerns have been consistently associated with greater negative reinforcement-related smoking motives and expectancies, [31,3739] whereas only one study has associated AS cognitive concerns with positive reinforcement-related smoking motives. [37] Although most studies have reported no relationship between AS facets and cigarette frequency or dependence severity, [31,38,39] one study reported that all three AS facets were associated with daily cigarette consumption.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations